The Effect of Audiovisual Media Toward Science and Behaviour of Malnutrion of Infant's Mother at Guntarano Village Tanantovea District of Donggala Regency - Nurul Pratiwi Lanipi; Firdaus J Kunoli; Muh Jufri (Universitas Muhammadiyah Palu, 2021)
Audiovisual media are media for information delivery with audio (sound) characteristics and visualÂ (picture. By selecting audiovisual media of health counseling, these media offer interesting counseling in which audiovisual media can facilitate information delivery or message from communicator to communicant. This research aims to determine the effect of audiovisual media on the science and behavior of malnutrition of an infant's mother at Desa Guntarano Tanantovea district of Donggala Regency. This quantitative research population is 35 people when all population members are used as a sample. Sample selection used the Non-Probability Sampling technique. Data analysis used simple linear regression with value Î±= 5%. Research findings show a significant effect between audiovisual media toward science and behavior of malnutrition of infant's mother with sig score 0,000 and 0,000 (Sig<0,05). It is suggested for mothers to be more active in seeking information about prevention so that infant's mother's malnutrition does not happen.